Pengaruh Penuaan Terhadap Karakteristik Paduan Ingat Bentuk Nitinol - Surian Pinem (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Nitinol is a form of alloy used for shaping memory applications because of its good mechanical properties and stable shape memory effect. The microstructure and transformation temperature is influenced by aging treatment, composition, and addition of elements to the alloy. This study explained the effect of aging treatment on the characteristic of Nitinol. The shape memory alloy with Ti-50.04 % at Ni composition was solution treated at 1000 oC for 1 hour and quenched in water, then aged in temperature of 500 oC, 550 oC, 600 oC, 650 oC and 700 oC for 10 hours. The microstructure was investigated using Scanning Electron Microscopy and mechanical property such as Vickers method. Transformation temperature was measured using resistance measurement technique. The result of microstructure observation showed that the martensitic phase was arranged by lamellar plates which tend to be softer in aging temperature, and the hardness decreased in aging temperature near 600OC - 700OC. The martensitic transformation temperature increased about 4 oC after aging process at 500 oC for 10 hours, but while aging temperature was near 500 oC – 700 oC, there was no significant change of the transformation temperature.Keywords: Shape Memory Alloy, Aging, Nitinol, Martensitic